Penerapan Total Quality Management dan Budaya Keselamatan Pasien untuk Meningkatkan Pencapaian Indikator Keselamatan Pasien Di RSU Gunung Sawo Temanggung - Luciana Dewi; Mus Aida; Nofi Erni (Syntax Corporation Indonesia, 2022)
Law No. 44 of 2009 concerning hospitals, hospitals are institutions that provide health services to the community so that hospitals are required to always provide services that prioritize patient safety. Patient safety incidents are still a major problem as an indicator of Quality Improvement and Patient Safety. The purpose of this study was to determine the application of Total Quality Management to achieve patient safety indicators and improve the quality of patient safety with Patient Safety Culture at Gunung Sawo Hospital, Temanggung. The study used a qualitative research approach. The quality improvement at Gunung Sawo General Hospital, Temanggung based on the research findings was carried out gradually getting better from day to day. The operational activities of non-medical personnel at RSU Gunung Sawo Temanggung run in accordance with established guidelines or regulations. Achievements and efforts to maintain improvements in quality and patient safety are carried out by Gunung Sawo Temanggung Hospital based on the results of quality achievements. Success is documented and made into a quality and patient safety report